Condition assessment methods for prestressed concrete railway sleepers: feasibility for South African applications - Lambrechs, Astrid (Department of Civil Engineering, 2025)
Concrete sleepers are a key component of railway systems, with estimates showing between 20 million to 35 million currently installed within the South African railway network. The condition assessment of concrete sleepers in South Africa poses a challenge for two main reasons: the scale at which condition measurements need to be conducted, and the poor access to sleepers within the ballast structure. To assess feasibility of concrete sleeper assessment methods, the quality of technical results was reviewed to ensure the information required for long-term lifecycle needs of concrete sleepers can be produced and that the risk associated with failures of critical defects are mitigated. The work established in the literature review was consolidated through a three-phase methodology to provide results for the assessment. This involved a Failure Mode and Effect Analysis (FMEA) that measured how well each of the methods can detect the failure modes, and then benchmarked the condition assessment methods against similar technology currently in use within the South African network. A test for defect relevance checked that the defects identified in the literature were relevant for South African applications and allowed for further categorisation of criticality. Longitudinal cracking and vertical cracks at the rail seat were found to be the most critical defects required to be detected by concrete sleeper condition assessment methods. Vehicle-mounted ultrasonic echo and vehicle-mounted imagining technology methods both showed good technical results from the FMEA, showing better quality information on sleeper condition than current methods in use. But only the vehicle-mounted imaging scored a residual profile value below the recommended technical threshold, and showed to benchmark cost, lead time and operational factors in line with current methods. Consequently, vehicle-mounted imaging is the most feasible option for concrete sleeper condition assessment for South African applications. Sleeper body abrasion cannot be well detected through any methods reviewed and will require further study of methods before visual inspections of this defect can be improved upon. Failure modes of concrete sleepers due to prestressing steel corrosion were unclear and further testing should be done to define what early-stage cracking displays to accurately predict the end of the useful life of a sleeper.